The impact of bedform migration on benthic oxygen fluxes. Issue 11 (14th November 2015) - Ahmerkamp, Soeren; Winter, Christian; Janssen, Felix; Kuypers, Marcel M. M.; Holtappels, Moritz
Abstract: Permeable sediments are found wide spread in river beds and on continental shelves. The transport of these sediments is forced by bottom water currents and leads to the formation of bedforms such as ripples and dunes. The bottom water flow across the bedforms results in pressure gradients that drive pore water flow within the permeable sediment and enhance the supply of reactive substrates for biogeochemical processes. This transport‐reaction system has been extensively studied for the case of stationary bedforms, whereas bedform migration—the most ubiquitous form of sediment transport—has been often ignored. To study the impact of sediment transport on pore water flow, we incorporated an empirical model of bedform migration into a numerical transport‐reaction model for porous media, using oxygen as reactive solute. The modeled oxygen flux changes significantly as soon as the sediment divides into an upper mobile layer (migrating bedform) and a stationary layer underneath. The bedform is increasingly flushed with oxic bottom water, whereas pressure gradients and pore water flow reverse at increasing rate underneath the bedform. This suppresses net pore water displacement and reduces the oxygen penetration depth up to 90%. In effect, the overall oxygen uptake decreases significantly with bedform migration although bottom water velocities increase. This counterintuitive effect is systematically described for a range of different sediment types, current velocities, and respiration rates and should be considered in future studies. Key Points: Bedform migration adds another mode of pore water transport Bedform migration strongly attenuates benthic fluxes Dispersion has a strong effect in case of bedform migration